Prospects of circadian clock in joint cartilage development. Issue 11 (18th September 2020) - Song, Xiaopeng; Hu, Hailong; Zhao, Mingchao; Ma, Tianwen; Gao, Li
Abstract: Altering the food intake, exercise, and sleep patterns have a great influence on the homeostasis of the biological clock. This leads to accelerated aging of the articular cartilage, susceptibility to arthropathy and other aspects. Deficiency or overexpression of certain circadian clock‐related genes accelerates the cartilage deterioration and leads to phenotypic variation in different joints. The process of joint cartilage development includes the formation of joint site, interzone, joint cavitation, epiphyseal ossification center, and cartilage maturation. The mechanism by which, biological clock regulates the cell‐cycle, growth, metabolism, and other biological processes of chondrocytes is poorly understood. Here, we summarized the interaction between biological clock proteins and developmental pathways in chondrogenesis and provided the evidence from other tissues that further predicts the molecular patterns of these protein‐protein networks in activation, proliferation, and differentiation. The purpose of this review is to gain deeper understanding of the evolution of cartilage and its irreversibility seen in damage and aging.